HUBUNGAN ANTARA KETUBAN MEKONIUM DENGANÂ KEJADIAN ASFIKSIA BAYI BARU LAHIR - Aris Lestari, Yufi; Luluk Arzukah, R. (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Meconium and amniotic newborn asphyxia cause high infant mortality rate. The condition of the baby is experiencing fetal distress before birth and due suck thick meconium into the lungs may experience an inability to breathe spontaneously and regularly in the first minute after birth. This study aimed to determine the relationship between amniotic meconium with newborn asphyxia.This study used a correlational design with retrospeksif approach. The population of 132 respondents. Variable research is meconium and amniotic newborn asphyxia. Samples were taken with a total sampling, data collection using medical record data is written in the observation sheet. Test the relationship of two variables with a correlation coefficient of contingency (C).The results showed 69 respondents (52%) newborns with meconium amniotic mild asphyxia (AS 7-10) number of 68 respondents (51.5%), moderate asphyxia (AS 4-6) number of 61 respondents (46.2%) and severe asphyxia occurs in three respondents (4.3%) with amniotic meconium. Test results obtained statistics there are strong positive relationship between amniotic fluid and meconium in the newborn asphyxia with significance level / significance 0,000(α <0.05) and correlation coefficient = 0.341 contingency.Based on these results, the necessary training and seminars to improve the skills of health workers, so that the handling and care of the newborn with amniotic meconium who suffered asphyxia, can be dealt with quickly and precisely, so that the death of a newborn baby can be minimized.Keywords: amniotic meconium, asphyxia, newborn